2018
DOI: 10.1123/ijspp.2018-0125
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Attack Performance in High-Level Male Volleyball Players

Abstract: 1Purpose: The volleyball attack is the action winning the majority of points during a game and 2 attack effectiveness (AE) is therefore one of the most important predictors of victory. 3Traditionally, greater vertical jump heights (VJH) and higher spike speeds (SS) have been 4 thought to increase AE, however relevant research is limited. Our aim was to assess the 5 relationship of VJH and SS with AE as well as identify possible associations of demographic 6 and anthropometric factors, including common volleyba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 12 publications
2
24
1
2
Order By: Relevance
“…Challoumas and Artemiou emphasized the importance of the score taken by the attack upon winning the match, and expressed that the studies to be carried upon developing vertical leaping and attack technique would improve the attack performance (Challoumas & Artemiou, 2018). Medeiros, Mesquita, Marcelino & Palao stated that attack efficiency was highly relational with the technique and age (Medeiros, Mesquita, Marcelino, & Palao, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Challoumas and Artemiou emphasized the importance of the score taken by the attack upon winning the match, and expressed that the studies to be carried upon developing vertical leaping and attack technique would improve the attack performance (Challoumas & Artemiou, 2018). Medeiros, Mesquita, Marcelino & Palao stated that attack efficiency was highly relational with the technique and age (Medeiros, Mesquita, Marcelino, & Palao, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The chance for a successful attack increases when all these factors are developed at a high level and the teams use varieties of attacks including numerous group tactics (Frohner, 1989;Sentuna, 2005). In volleyball, the teams win most of the scores from the attacks; therefore, efficieny of the attack is one of the most important determinants of victory (Challoumas & Artemiou, 2018).…”
mentioning
confidence: 99%
“…Based on the data obtained with the questionnaire, an important result to be highlighted was to verify that all information contained in the questionnaire, even with different proportions, may interfere with the DM process of the setters. Thus, in volleyball, the setter's DM might be dependent of the interaction of various technical and tactical factors 32 , and not just the individual capacity of the attacker 14,16 , psychological constraints 14 or even physical factors, as highlighted by Challoumas and Artemiou 33 who, in their studies, found a correlation between attack efficiency and anthropometric factors. In this sense, when investigating the DM of setters, authors should consider that it might be influenced by different, varied factors.…”
Section: Discussionmentioning
confidence: 99%
“…Volleyball players' jump skills should be higher than average to beat their opponents and to be successful. Since, jumping skill is one of the most important disputable reason which affects the success in volleyball, according to volleyball coaches and players (Sheppard, Newton, & McGuigan, 2007;Challoumas & Artemiou, 2018;Kitamura et al, 2017).…”
Section: Discussionmentioning
confidence: 99%